ANALYSIS OF ALTERNATIVE LOCATIONS FOR STREET VENDORS TOUR IN PAYAKUMBUH CITY - Fitriana Syahar; Ririn Aurelia N (The Tourism, Heritage and Recreation Sport Center, Universitas Negeri Padang, 2020)
This study aims to: Analyze the alternative locations of street vendors for buyers using the breaking point method. This type of research is descriptive with a quantitative approach using primary data and secondary data obtained through observation, interviews, questionnaires and documentation. Respondents of this study were 75 street vendors who were on Jalan Soekarno-Hatta to Jalan Jendral Sudirman, Payakumbuh market. The data analysis technique used is the data analysis technique using the Breaking Point method. This study found: The alternative location of street vendors for buyers originating from Pekanbaru City is 45 km from the merchant's location, the alternative location of street vendors is seen from the distance of the stopping points for buyers from Bukittinggi 7 km, and alternative locations for street vendors as seen from the stopping point distance of buyers originating from Batusangkar is 6 km from the location of the street vendors.